Governance and policy capacity in health development and implementation in Australia. Issue 3 (September 2015) - Hughes, A.; Gleeson, D.; Legge, D.; Lin, V.
Abstract: This article examines policy capacity in the context of Australian health authorities in relation to the challenges confronting policy workers and senior managers in these agencies. The article reports the challenges identified by our informants in relation to political structures, roles and responsibilities of other portfolios and governments, interactions between policy officials and with the minister and the minister's office, whole of government policy approaches, stakeholder and public demands and expectations, and media pressures. The experience of these senior managers and policy workers is then reinterpreted in terms of a nodal governance model. The findings from the Australian study on policy capacity, interpreted in the context of nodal governance, is then used to discuss the features of "governance capacity" as articulated in the matrix model of policy capacity developed byWu, Ramesh and Howlett (2015) . The article concludes with propositions for strengthening policy capacity across the governance regime so depicted. These include: capacity building for individuals at various key locations in the network; organisational capacity building within the organisations and across their key relationships; and reforms across the governance network as a whole.